Penerapan Data Pipeline untuk Meningkatkan Efisiensi Penghitungan Indeks Perkembangan Harga (IPH) di Indonesia - Sandyawan, Ignatius; Rimawati, Yeni; Suarjaya, I Made Oka (Politeknik Statistika STIS, 2024)
The Price Change Index (PCI) is an indicator for monitor market price fluctuations. In 2022, Statistics Indonesia (BPS), worked with Ministry of Home Affairs (Kemendagri) as data steward and the Ministry of Trade (Kemendag) as a data collector, to calculate the PCI for 20 primary commodities across all cities in Indonesia. Weekly price data was collected by city trade departments and transferred to BPS for processing. Until late 2023, this process, done in Microsoft Excel, could take up to three days and was prone to errors. This research focuses on implementing a data pipeline for PCI calculations, automating tasks like data cleaning, index calculation, and visualization. Results showed the data pipeline reduced calculation time to just 16 minutes while maintaining consistency with manually obtained PCI values. The implementation has significantly improved time efficiency, minimized errors, and optimized resource use.